Gene Editing and Human iPSCs in Cardiovascular and Metabolic Diseases - Giallongo, Sebastiano; Lo Re, Oriana; Resnick, Igor; Raffaele, Marco; Vinciguerra, Manlio (Advances in experimental medicine and biology, 2023)
The incidence and the burden of cardiovascular disease (CVD), coronary heart disease (CHD), type 2 diabetes mellitus (T2DM), and the metabolic syndrome are greatly increasing in our societies. Together, they account for 31% of all deaths worldwide. This chapter focuses on the role of two revolutionary discoveries that are changing the future of medicine, induced pluripotent stem cells (iPSCs) and CRISPR/Cas9 technology, in the study, and the cure of cardiovascular and metabolic diseases.We summarize the state-of-the-art knowledge about the possibility of editing iPSC genome for therapeutic applications without hampering their pluripotency and differentiation, using CRISPR/Cas technology, in the field of cardiovascular and metabolic diseases.
Keywords: kardiovaskulární systém; Humans; Gene Editing; Epigenetics; Metabolism; Diabetes Mellitus, Type 2; metabolické nemoci; Cardiovascular System; Gene editing; Induced Pluripotent Stem Cells; diabetes mellitus 2. typu; indukované pluripotentní kmenové buňky; Metabolic Diseases; Induced pluripotent stem cells (iPSC); Cardiovascular; lidé; editace genu